Valencia CF and the recovery of sports relations between Spain and Mexico (1954-1966) - Josep Andreu Bosch Valero; José Ricardo March Arnao (Universidad Politécnica de Madrid, 2024)
Between 1963 and 1966, the Spanish club Valencia Club de Fútbol visited Mexico on two occasions, a country with which Spain had not maintained diplomatic relations since the end of the Civil War in 1939 and where numerous Spanish Republican exiles lived. In the expatriate colony, the presence of Valencian citizens stood out, organized in a Regional House, who, in coordination with the Valencia board of directors, promoted the visit of the club from their city of origin. Among the most outstanding milestones of these two expeditions, on the sporting level, the participation of the club in the inauguration acts of the Azteca Stadium and, on the social and political aspect, the resumption, in the midst of the Franco dictatorship, of relations with the exiled. This work is based on the analysis of private archives, Spanish and Mexican newspaper sources and abundant bibliography on the Spanish exile in the Central American country and allows us to conclude that the two tours were essential to normalize sports relations between both countries.